2020
DOI: 10.1186/s12885-020-6704-z
|View full text |Cite
|
Sign up to set email alerts
|

Dissociated responses at initial computed tomography evaluation is a good prognostic factor in non-small cell lung cancer patients treated with anti-programmed cell death-1/ligand 1 inhibitors

Abstract: Background: Dissociated responses (DR) are phenomena in which some tumors shrink, whereas others progress during treatment of patients with cancer. The purpose of the present study was to evaluate the frequency and prognosis of DR in non-small cell lung cancer (NSCLC) patients treated with anti-programmed cell death-1/ligand 1 (anti-PD-1/L1) inhibitors. Methods: This retrospective study included NSCLC patients who received anti-PD-1/L1 inhibitor as second-or laterline treatment. We excluded patients without ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 27 publications
(33 reference statements)
2
25
0
Order By: Relevance
“…By demonstrating the discordant treatment effects between primary sites and adjacent nodes, this study achieves several ends. First, it supports the findings of other studies demonstrating similar discordance in other solid malignancies, such as lung cancer ( 10 , 11 ). Importantly, however, unlike the aforementioned studies, this research utilizes the gold standard of tumor progression, histopathology, to compare true treatment effect to that which is demonstrated by CT imaging.…”
Section: Discussionsupporting
confidence: 89%
“…By demonstrating the discordant treatment effects between primary sites and adjacent nodes, this study achieves several ends. First, it supports the findings of other studies demonstrating similar discordance in other solid malignancies, such as lung cancer ( 10 , 11 ). Importantly, however, unlike the aforementioned studies, this research utilizes the gold standard of tumor progression, histopathology, to compare true treatment effect to that which is demonstrated by CT imaging.…”
Section: Discussionsupporting
confidence: 89%
“…Atypical patterns (pseudo-progression + dissociated response) were associated with a better overall survival than true progressions. Another retrospective study including 62 NSCLC patients also observed a dissociated response in 9.2% of patients treated with PD-1/L1 inhibitors, and confirmed the improved OS associated to this pattern compared to homogenous progression (14.0 vs. 6.6 months) (14).…”
Section: Immunotherapies In Solid Cancermentioning
confidence: 62%
“…Third, target lesions selected for calculation of TGR might not represent the whole tumor burden as new lesions and non-target lesions were not taken into account. Dissociated or mixed response phenomenon may confound the accurate tumor kinetics assessment after treatment initiation (32). Fourth, Limited to the retrospective nature of our work, we were unable to estimate predictive value of PD-L1 status and TMB level for only 3 patients had detected these two items.…”
Section: Discussionmentioning
confidence: 88%